Employees' perceptions of corporate social responsibility and ethical leadership: are they uniquely related to turnover intention?. Issue 2 (10th February 2020) - Nejati, Mehran; Brown, Michael E.; Shafaei, Azadeh; Seet, Pi-Shen
Abstract : Purpose: The purpose of this study is to investigate the simultaneous effect of ethical leadership (EL) and corporate social responsibility (CSR) on employees' turnover intention and examine the mediating mechanism in these relationships. Design/methodology/approach: The authors conducted a field study of 851 employees across a variety of industries. This study applied partial least squares structural equation modelling for hypothesis testing. Findings: The results show that employees' perceptions of CSR as well as EL are both uniquely and negatively related to turnover intention. The authors also found that employees' job satisfaction but not commitment, mediates these relationships. Research limitations/implications: This study answers the recent call (Schminke and Sheridan, 2017) for ethics researchers to put competing explanations to the test to determine their relative importance. Research limitations have been discussed in the paper. Social implications: Through providing empirical support for the positive impact of CSR and EL on employee-related outcomes and creating a decent and empowering work environment, this study provides further support for CSR and EL. As CSR and EL require accountability, responsible management and addressing societal well-being of stakeholders, this study can contribute to the United Nations sustainable development goals. Originality/value: Previous research has found that both employees' perceptions of supervisory EL and CSR are negatively related to employees' turnover intentions. Yet, researchers know little about their relative importance because these relationships have not been adequately examined simultaneously.